Modelling and Simulation of Inventory Replenishment Policies and Comparison of Target Days Vs Actual Days of Inventory Held - Anthony Vaz; Anwar Tedjamulja; Shadi Kafi Mallak; Premkumar Rajagopal (International Journal of Supply Chain Management, 2020)
Supply chain managers often apply aggregate planning techniques to develop make or buy decisions or even make for stock versus make to order scenarios for example. These scenarios often contain combinations of inventory holding vs capacity installed. Many supply chain managers have used ‘what-if’ decisions to develop supply chain scenarios to help them determine optimum results in terms of low cost and improved customer service. This study aims to create eight scenarios of varying inventory replenishment policies for one fast moving consumer goods (FMCG) organisation. The aim is to provide the supply chain manager with alternative options for lower inventory and yet be able to service the FMCG businesses at lowest cost. The results show that this allows supply chain managers to pick the scenario that optimises an organisation’s resources and competitive strategy.